Multimedia learning: advantages and disadvantages - Arina V. Banartseva; Alla A. Nechaeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Education technologies have done a great deal to help teachers support students. Multimedia learning is the use of technology to support the learning process. Using multimedia in the teaching and learning environment enables students to become critical thinkers, problem solvers, more motivated in their learning processes. English is a content best mastered through students’ discovering and working through their own various curricular initiatives, so students need to take an ownership and responsibility for their own learning.The paper provides a brief overview of the advantages and disadvantages of learning via Skype and gives the example of exercises used. The major educational benefit is in meeting the needs of the students who make decision of learning autonomously.